ANCIENT TEXTS, MODERN APPLICATIONS: CONTEXTUALIZING BIBLICAL PRINCIPLES IN TODAY'S MINISTRY - Kirolos Eskandar (Caminhos)
In an era marked by rapid cultural evolution and societal transformation, the challenge for ministry leaders lies in bridging the gap between the timeless teachings of biblical scripture and the complexities of contemporary life. The principles contained within ancient texts are universally acknowledged for their wisdom on human morality, justice, and ethical living. However, the contextualization of these teachings in modern settings requires a nuanced approach that respects both the original intent of scripture and the realities of today's world. This literature review seeks to explore the process of translating biblical principles into actionable frameworks for modern ministry. By examining the distinction between enduring truths and culturally bound practices, as well as considering emerging trends in digital ministry and creative outreach, this article provides an insightful guide for ministry professionals aiming to apply scripture faithfully and effectively in current contexts.